Development of Alphabetic Cards as A Learning Medium for the Community Learning Activity Center Community - Pinontoan, Marien; Wullur, Mozes Markus; Dumanaw, Ronny G.; Rahmat, Abdul (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
The development of the Out-of-School Education sector has a strategic role in improving the quality of human resources. Learning media in alphabet cards is needed to increase students' motivation and learning achievement in reading learning, which are used as a learning resource to develop learning models while playing for students. This research aims to determine and test the effectiveness of implementing the development of the learning process for reading while playing through alphabet card learning media for residents learning literacy in PKBM North Sulawesi Province. This research uses the "Research and Development" method, following the research stages of developing the ADDIE model (Analyze, Design, Develop, Implement, and Evaluate) in 4 districts: 1). Bolaang Mongon-dow South, 2). East Bolaang Mongondow, 3). Talaud Islands, and 4). North Minahasa. This research was designed for two years, and in the first year, 2022, it was carried out in 3 stages: 1). Analysis Stage, 2). Design stage, and 3). Development Stage. Meanwhile, two stages were carried out for the second year, namely the Implementation and Evaluation stages. It can be concluded that the learning process is effective because students who were previously literate but forgot the letters have learned them again. There is an increase in students' cognitive abilities, better ability to arrange letters to form meaningful words, and students' learning becoming more involved.